Role of ADAMTS5 in Unexplained Fetal Growth Restriction (FGR). (3rd July 2016) - Ozler, Sibel; Oztas, Efser; Guler, Basak Gumus; Pehlivan, Sultan; Kadioglu, Nezaket; Ergin, Merve; Uygur, Dilek; Danisman, Nuri
ABSTRACT: Aim : We aim to determine the role of serum and placental A disintegrin and metalloproteinase with thrombospondin motif 5 (ADAMTS5) in fetal growth restriction (FGR). Material and Methods : 43 pregnancies suffering FGR and 45 healthy ones were homogenized for their body mass indices, ages, and gestational weeks. Expression of ADAMTS5 in placental samples was determined by immunohistochemical methods and concurrent maternal serum ADAMTS5 levels were determined with enzyme-linked immunosorbent assay. Results : Expression of ADAMTS5 was higher in FGR group than the healthy control in placenta. Both the cytoplasmic staining pattern of the syncytiotrophoblasts and staining of the decidual plate were shown in the FGR group; but not in the control group. A negative correlation between serum ADAMTS5 levels and birth weight in FGR group was observed. Conclusion : Increased ADAMTS5 levels were observed in placental insufficiency cases. This study demonstrates that ADAMTS5 may be a sensitive indicator of placental insufficiency which has variable factors in etiology. Additional work is needed to delineate the mechanism of its involvement.